2012
DOI: 10.4161/cc.21277
|View full text |Cite
|
Sign up to set email alerts
|

The BTB-ZF transcription factors

Abstract: T he BTB-ZF (broad-complex, tramtrack and bric-à-brac -zinc finger) proteins are encoded by at least 49 genes in mouse and man and commonly serve as sequence-specific silencers of gene expression. This review will focus on the known physiological functions of mammalian BTB-ZF proteins, which include essential roles in the development of the immune system. We discuss their function in terminally differentiated lymphocytes and the progenitors that give rise to them, their action in hematopoietic malignancy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 137 publications
3
111
0
Order By: Relevance
“…MAZR, a member of the BTB-Pox virus and ZF domain containing a family of ZF transcription factors (23,24), is part of the transcription factor network regulating CD4/CD8 cell fate choice of DP thymocytes by repressing Thpok expression in MHC class I-signaled DP thymocytes (13). We observed that MAZR interacts with Runx proteins and hypothesized that MAZR and Runx/CBFb complexes might synergize in the repression of ThPOK (13).…”
Section: Mazr Interacts With the Ad Of Runx1 Via Zf7mentioning
confidence: 90%
“…MAZR, a member of the BTB-Pox virus and ZF domain containing a family of ZF transcription factors (23,24), is part of the transcription factor network regulating CD4/CD8 cell fate choice of DP thymocytes by repressing Thpok expression in MHC class I-signaled DP thymocytes (13). We observed that MAZR interacts with Runx proteins and hypothesized that MAZR and Runx/CBFb complexes might synergize in the repression of ThPOK (13).…”
Section: Mazr Interacts With the Ad Of Runx1 Via Zf7mentioning
confidence: 90%
“…PATZ1 has an N-terminal BTB domain for protein interaction, a central DNA binding AT hook domain, and a second, C-terminal, zinc finger (ZF) DNA binding domain (9)(10)(11). A recent ChIP-Seq study identified that the PATZ1 binding consensus can be either AT rich or GC rich (12).…”
mentioning
confidence: 99%
“…The most down-regulated transcript in our data set, zinc finger and BTB domain-containing protein 16 (ZBTB16) was originally identified as a fusion partner of the retinoic acid receptor α (RARα) in acute promyeloid leukemia (Chen et al, 1993). ZBTB16 is a member of the promyelocytic leukemia zinc finger (PLZF) family of which factors are shown to be critically involved in the hematopoietic differentiation acting as sequence-specific silencers of gene expression (Siggs and Beutler, 2012). In our data set, we have 4 dysregulated members of PLZF family indicating that chronic TCDD exposure in our model was associated with profound transcriptional remodeling, consistent with the growing realization of the AhR involvement in the wide scale epigenetic remodeling (Tian, 2009).…”
Section: Discussionmentioning
confidence: 99%